Modelado del proceso de soldadura Smaw por medio del método de elementos finitos - Sánchez Salas, Kevin Manuel (2019)
In this research, we sought to model the heat transfer process in a butt welded joint using the finite element method. We worked with AISI 1020 Steel and AISI 1040 Steel due to its constant use in local and national industry. A program was carried out to obtain the distribution of Temperatures, cooling curves and Phase transformations for each of the aforementioned steels. It was found that the transfer results are very similar in both cases due to their thermal properties, however Phase Transformations vary the percentages due to their composition. With these results, some mechanical properties of welded joints can be predicted.